If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 1)(7x + -6) = 0 Reorder the terms: (1 + 4x)(7x + -6) = 0 Reorder the terms: (1 + 4x)(-6 + 7x) = 0 Multiply (1 + 4x) * (-6 + 7x) (1(-6 + 7x) + 4x * (-6 + 7x)) = 0 ((-6 * 1 + 7x * 1) + 4x * (-6 + 7x)) = 0 ((-6 + 7x) + 4x * (-6 + 7x)) = 0 (-6 + 7x + (-6 * 4x + 7x * 4x)) = 0 (-6 + 7x + (-24x + 28x2)) = 0 Combine like terms: 7x + -24x = -17x (-6 + -17x + 28x2) = 0 Solving -6 + -17x + 28x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -4x)(6 + -7x) = 0Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25Subproblem 2
Set the factor '(6 + -7x)' equal to zero and attempt to solve: Simplifying 6 + -7x = 0 Solving 6 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -7x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -7x = 0 + -6 -7x = 0 + -6 Combine like terms: 0 + -6 = -6 -7x = -6 Divide each side by '-7'. x = 0.8571428571 Simplifying x = 0.8571428571Solution
x = {-0.25, 0.8571428571}
| 5x^2-7+2=0 | | 9x+1=3x+31 | | (2x+4)*(x-1)-36=0 | | 180x^4-108x^3-107x^2+36x+20=0sol | | 4x=46-10 | | 3(2x+1)+5=7-3x | | 9x-7=-2x+-40 | | 4/5c•4c/18 | | 7x-8=9x+(2) | | Ln(2.5x)=3 | | 13x-66=90 | | 3x+5y-7x=37findx | | y^2+2y+x^2-24=14 | | 9x+2=7x+-14 | | 10x-20=7x+10 | | 6x+56+10=180 | | 0.9/COS | | 5(3x+5)=4(3x+4)+3 | | -5(5-x)+4=3(x-1) | | (-2x)/(12x) | | 2(3x+5)=4(x-5)+2x | | -2x/12x | | 6x+3=-3x+-60 | | 4(2x-2)=3(5x-3) | | -2b+8=-15 | | -198=-18x | | 6(x-4)=3(2x-5) | | 4(3-x)-(12+x)=4 | | p+1=11 | | -6(1)+2= | | 6=-2x+64 | | -6(2)+2= |